A Prospective Study of Ripple Mapping in Atrial Tachycardias: A Novel Approach to Interpreting Activation in Low-Voltage Areas. (January 2016) - Luther, Vishal; Linton, Nick W.F.; Koa-Wing, Michael; Lim, Phang Boon; Jamil-Copley, Shahnaz; Qureshi, Norman; Ng, Fu Siong; Hayat, Sajad; Whinnett, Zachary; Davies, D. Wyn; Peters, Nicholas S.; Kanagaratnam, Prapa
Abstract : Background—: Post ablation atrial tachycardias are characterized by low-voltage signals that challenge current mapping methods. Ripple mapping (RM) displays every electrogram deflection as a bar moving from the cardiac surface, resulting in the impression of propagating wavefronts when a series of bars move consecutively. RM displays fractionated signals in their entirety thereby helping to identify propagating activation in low-voltage areas from nonconducting tissue. We prospectively used RM to study tachycardia activation in the previously ablated left atrium. Methods and Results—: Patients referred for atrial tachycardia ablation underwent dense electroanatomic point collection using CARTO3v4. RM was played over a bipolar voltage map and used to determine the voltage "activation threshold" that differentiated functional low voltage from nonconducting areas for each map. Ablation was guided by RM, but operators could perform entrainment or review the isochronal activation map for diagnostic uncertainty. Twenty patients were studied. Median RM determined activation threshold was 0.3 mV (0.19–0.33), with nonconducting tissue covering 33±9% of the mapped surface. All tachycardias crossed an isthmus (median, 0.52 mV, 13 mm) bordered by nonconducting tissue (70%) or had a breakout source (median, 0.35 mV) moving away from nonconducting tissue (30%). In reentrant circuits (14/20) the path length was measured (87–202 mm), with 9 of 14 also supporting a bystander circuit (path lengths, 147–234 mm). In breakout tachycardias, splitting of wavefronts resulted in 2 to 4 incomplete circuits. RM-guided ablation interrupted the tachycardia in 19 of 20 cases with the first ablation set. Conclusions—: RM helps to define activation through low-voltage regions and aids ablation of atrial tachycardias. Abstract : Supplemental Digital Content is available in the text.